Elevated Systemic Neutrophil Count in Diabetic Retinopathy and Diabetes: A Hospital-Based Cross-sectional Study of 30,793 Korean Subjects - Woo, Se Joon; Ahn, Seong Joon; Ahn, Jeeyun; Park, Kyu Hyung; Lee, Kiheon (Investigative ophthalmology & visual science, 2011)
To evaluate the association between systemic parameters including inflammatory markers and diabetic retinopathy (DR). This was a cross-sectional study enrolling 30,793 persons who visited a health care center for a medical checkup. Diabetic patients were classified into five DR groups: no DR; mild, moderate, or severe nonproliferative DR, and proliferative DR. A full laboratory workup and comprehensive medical data on the subjects were obtained and used for analysis. The mean (SD) age of the participants was 47.4 (11.9) years (range, 18-90) and the male-to-female ratio was 55.7:44.3. The prevalence of diabetes and DR were 6.6% (2,020/30,793) and 5.3% (108/2,020), respectively. Among inflammatory markers, the mean absolute neutrophil count (ANC; per microliter) was significantly higher in the DR than in the non-DR group (3900 vs. 3566; P = 0.0143) and in diabetic than in nondiabetic subjects (3583 vs. 3262; P < 0.0001). Subjects in the fourth quintiles of ANC showed 2.7 odds of having DR by multivariate analysis, and there was a linear trend in the odds ratios according to increasing ANC levels. The level of ANC and the ANC/leukocyte ratio also demonstrated a linearly increasing trend with the severity of DR, even after adjustment for other clinical factors, including HbA1c. Among significant risk factors of DR, ANC showed the second strongest predictive power for DR (AUROC = 0.590) after HbA1C (0.624). Elevated systemic neutrophil count is associated with the presence and severity of DR as well as diabetes. This result indicates that systemic subclinical inflammation is related with DR, and neutrophil-mediated inflammation may play an important role in the pathogenesis of DR.